High-Flow Oxygen Therapy During Exercise Training in Patients With Chronic Obstructive Pulmonary Disease and Chronic Hypoxemia: A Multicenter Randomized Controlled Trial. Issue 8 (24th April 2020) - Vitacca, Michele; Paneroni, Mara; Zampogna, Elisabetta; Visca, Dina; Carlucci, Annalisa; Cirio, Serena; Banfi, Paolo; Pappacoda, Gabriele; Trianni, Ludovico; Brogneri, Antonio; Belli, Stefano; Paracchini, Elena; et al.
Abstract: Objective: The study aimed to evaluate whether high-flow oxygen therapy (HFOT) during training was more effective than oxygen in improving exercise capacity in hypoxemic chronic obstructive pulmonary disease (COPD). Methods: A total of 171 patients with COPD and chronic hypoxemia were consecutively recruited in 8 rehabilitation hospitals in a randomized controlled trial. Cycle-ergometer exercise training was used in 20 supervised sessions at iso inspiratory oxygen fraction in both groups. Pre- and post-training endurance time (Tlim), 6-minute walking distance (6MWD), respiratory and limb muscle strength, arterial blood gases, Barthel Index, Barthel Dyspnea Index, COPD Assessment Test, Maugeri Respiratory Failure questionnaire, and patient satisfaction were evaluated. Results: Due to 15.4% and 24.1% dropout rates, 71 and 66 patients were analyzed in HFOT and Venturi mask (V-mask) groups, respectively. Exercise capacity significantly improved after training in both groups with similar patient satisfaction. Between-group difference in post-training improvement in 6MWD (mean: 17.14 m; 95% CI = 0.87 to 33.43 m) but not in Tlim (mean: 141.85 seconds; 95% CI = −18.72 to 302.42 seconds) was significantly higher in HFOT. The minimal clinically important difference of Tlim was reached by 47% of patients in the V-mask group and 56% of patients in the HFOT group, whereas the minimal clinically important difference of 6MWD was reached by 51% of patients in the V-mask group and 69% of patients in the HFOT group, respectively. Conclusion: In patients with hypoxemic COPD, exercise training is effective in improving exercise capacity. Impact Statement: The addition of HFOT during exercise training is not more effective than oxygen through V-mask in improving endurance time, the primary outcome, whereas it is more effective in improving walking distance.